Hybrid learning and continuing education : 6th International Conference, ICHL 2013, Toronto, ON, Canada, August 12-14, 2013. Proceedings - Fong, Joseph; Fong, Wilfred; Wang, Fu Lee; Kwok, Lam For; Cheung, Simon K. S. (Lecture notes in computer science, 2013)
This book constitutes the refereed proceedings of the 6th International Conference on Hybrid Learning, ICHL 2013, held in Toronto, ON, Canada, in August 2013. The 35 papers presented in this volume were carefully reviewed and selected from numerous submissions. The selected articles broadly cover topics on hybrid learning and continuing education, including computer supported collaborative learning, experiences in hybrid learning, pedagogical and psychological issues, e-learning and mobile learning, open education resources and open online courses, and issues in hybrid learning and continuing education.